If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+1/4-3=5x-4/3
We move all terms to the left:
3x+1/4-3-(5x-4/3)=0
We add all the numbers together, and all the variables
3x-(+5x-4/3)-3+1/4=0
We get rid of parentheses
3x-5x-3+4/3+1/4=0
We calculate fractions
There is no solution for this equation
| 2.4/x=3/4.5 | | X+.07x=97.26 | | 7x+7=11x-25 | | 7x+7=(11x-25) | | (7x+7)=(11x-25) | | 3(2x-4)=-5(x-2) | | 2x-(3x-4)=11 | | 5t=-3=2t+5 | | 6x(5)+4+1(6)=2x-3(10) | | 4m^2+5m+7=0 | | 2a-48=5a | | s/6.2s+14.18=–37.28 | | -1-22n=-20-9 | | x(3x-5)(2x-19)=180 | | 20n(n+2)=9n-12 | | x+(5x+19)+x=180 | | -5+31=-14n-5 | | 7^x=(1/49)^(x+3) | | 6=12-x/3 | | -4x+(-9)x+19=15+10 | | 102=1.2•w | | 3x+x+75=180 | | -4=8-2/3*x | | T(n)=2(n+1) | | 2x+x=+10+11 | | 300=51•p | | -4=8-2/3x | | 5z-2=28 | | -x/4+5=9 | | -2x+9=1/3x-26 | | 0.005=wX12 | | 12-6x=-4x+18 |